A incidência do ITBI em integralização de capital, quando a atividade do adquirente é preponderantemente imobiliária - Lopes, Julia Rodrigues (2023)
The article 156, §2º, item I of the Federal Constitution provides for two hypotheses of ITBI tax immunity, at the end, establishes an exception rule: If the main activity of the legal entity acquirer is real estate, there will be no immunity. Until then the consolidated understanding was in the sense that the two hypotheses of immunity provided for in the constitutional provision are conditioned to this exception rule. It means that the real estate purchaser, exercise predominantly real estate activity, cannot benefit from ITBI immunities. Although,in the judgment of the Extraordinary Appeal (EA) nº 796.376/SC, tangentially to the merits of the specific case,the Minister Alexandre de Moraes concluded that the exception rule corresponds only to the second hypothesis of immunity described by the constitutional article. By this reasoning the first immunity which corresponds to the transfer of real estate to the company's equity in the realization of capital would be unconditioned. In this way, there would be no incidence of ITBI even though the main activity of the acquirer is real estate. Therefore, due to the new understanding, the present study aims to analyze whether the exception provided for in the final part of article 156, §2º, item I of the Federal Constitution still covers the two hypotheses of immunity inserted in said device. Therefore, in the present work, an analysis of the effects of the interpretation adopted by the Minister Alexandre de Moraes seeking to identify to what extent the decision may impact taxpayers considering that this is a significant change of understanding. At end, it was concluded that, despite there being no binding effect because it is an obiter dictum basis in the vote was relevant insofar as it paved the way so that taxpayers can seek to be contemplated by the immunity of ITBI in the payment of capital, even when the activity is predominantly real estate. So, observing the municipal legislation it is up to the Judiciary to decide in each case, until a pacified understanding is reached.